Pemberdayaan Pemberdayaan Karang Taruna Desa Gampingrowo dengan Pelatihan Hidroponik - Erlinda Ningsih; Agus Budianto; Kartika Udyani; Yustia Wulandari M; Shofiyya Julaika; Dian Yanuarita P (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of the property industry is very influential on the agricultural sector. Gampingrowo Village is an area where most of the people earn their living from agriculture. This relates to the availability of land if the land is used for the property industry. One alternative to overcome the limitations of agricultural land is to apply agricultural cultivation technology with the hydroponic method. The purpose of this service is to provide youth with skills, knowledge about hydroponics. This training method is carried out by providing counseling on hydroponic methods in general and training participants practice to assemble simple starter kits. Participants 25 people were divided into 3 groups where each group got 2 starter kit packages. The results of this dedication were that the participants were very enthusiastic and eager to know more about the hydroponic method with a few questions and they were very happy because the starter kit could be taken home